Assessment of water pollution induced by human activities in Burullus Lake using Landsat 8 operational land imager and GIS - Ahmed El-Zeiny; Sameh El-Kafrawy (Egyptian Journal of Remote Sensing and Space Sciences, 2017)
Burullus Lake is the second largest lake along the Mediterranean Sea and represents one of the most subjected lakes to pollution at the delta’s coastline. The present study explores the use of Landsat data and GIS for assessing water pollution at Burullus Lake, Egypt. Multi-spectral Landsat-8 OLI image dated 2015 provided the necessary information to this study. Radiometric and atmospheric corrections were applied to the image. Land use/cover map was obtained to identify natural resources and types of human activities in the area surrounding the Lake. Three previously developed water quality empirical models for BOD, total nitrogen (TN) and total phosphorus (TP) were applied on the calibrated image. Then, a GIS model was generated to identify areas recording high levels of BOD, TN and TP. Results confirmed that the Lake water is subjected to pollution from multiple sources; particularly domestic and agricultural drains. Shallow water (i.e. Lake Shores), where human activities are influencing, reported high levels of water studied pollutants. The model indicated that south western and north eastern parts of the Lake are the most polluted parts, recording relatively high levels of BOD, TN and TP; >4.46 mg L−1, >18.33 mg L−1 and >15.59 mg L−1, respectively. Results were ascertained based on water quality investigations in relevant research studies on the Lake. It was concluded that Burullus Lake is extensively subjected to interrupting human activities which have a great negative impact on water quality. Also data-observation techniques and water quality empirical models were successful in assessing and mapping water pollution.